Impostor phenomenon short scale (IPSS-3): a novel measure to capture impostor feelings in large-scale and longitudinal surveys - Jansen, Max P. (Frontiers in Psychology, 2024)
The Imposter Phenomenon (IP) is gaining increasing attention in academia, not only as an overall attractive research topic but also as a concern that especially affects members of minority groups. Nevertheless, there is little evidence for the occurrence and socio-structural correlates of the IP. Against the backdrop of a pressing need to contextualize the IP, this paper provides (1) an overview of the existing empirical evidence on the IP from a perspective that incorporates the role of social contexts, (2) highlights shortcomings in both existing theoretical approaches and methodological tools, (3) introduces the Impostor Phenomenon Short Scale (IPSS-3) as a novel, time-efficient and universally applicable IP measure, and (4) underscores that the IP, in fact, does not occur in a social vacuum but is closely intertwined with socio-structural characteristics. To this end, the paper draws on three distinct data sets gathered among German adolescents and adults for the development of the IPSS-3 (Study 1: n = 271), its validation (Study 2: n = 427), and to assess the IP's socio-structural correlates (Study 3: n = 865). The findings demonstrate that the IPSS-3 represents the first timeefficient and universally applicable instrument suitable for capturing the IP in large-scale and longitudinal research designs, e.g., initiated in adolescence. Thus, the IPSS-3 can address key open questions related to age effects, the role of transitions in the life course, and systematic variations in IP intensity among different social groups.